2005
DOI: 10.1016/j.cardiores.2005.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil attenuates cardiac hypertrophy in lipotoxic cardiomyopathy due to systemic carnitine deficiency

Abstract: Dietary FO may attenuate cardiac hypertrophy with improvements in cardiac function and survival in JVS mice via modification of the molecular species composition of myocardial DAG and the consequent inhibition of PKC redistribution. These results suggest the implication of the molecular species composition of DAG in the pathogenesis of lipotoxic cardiomyopathy due to perturbations of fatty acid beta-oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…However, in mice subjected to AAC, the myocardial triacylglycerol level was significantly reduced to identical levels in both WT and jvs/ϩ mice, and the 1,2-diacylglycerol level in jvs/ϩ mice was significantly reduced to WT mice levels. In contrast to the dramatic alteration of the fatty acid composition of myocardial 1,2-diacylglycerol in homozygous JVS mice as demonstrated in our previous reports, 9,15,23,32 jvs/ϩ-sham mice did not show significant alteration in the fatty acid composition of 1,2-diacylglycerol. Although mice subjected to AAC showed changes in fatty acid composition of myocardial 1,2-diacylglycerol compared with sham-operated mice, there was no difference between WT-AAC and jvs/ϩ-AAC mice.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…However, in mice subjected to AAC, the myocardial triacylglycerol level was significantly reduced to identical levels in both WT and jvs/ϩ mice, and the 1,2-diacylglycerol level in jvs/ϩ mice was significantly reduced to WT mice levels. In contrast to the dramatic alteration of the fatty acid composition of myocardial 1,2-diacylglycerol in homozygous JVS mice as demonstrated in our previous reports, 9,15,23,32 jvs/ϩ-sham mice did not show significant alteration in the fatty acid composition of 1,2-diacylglycerol. Although mice subjected to AAC showed changes in fatty acid composition of myocardial 1,2-diacylglycerol compared with sham-operated mice, there was no difference between WT-AAC and jvs/ϩ-AAC mice.…”
Section: Discussionmentioning
confidence: 38%
“…9,15,23,32 In the present study, we have also carried out myocardial lipid analysis in heterozygous JVS mice subjected to pressure overload (Table S2). In contrast to homozygous JVS mice, jvs/ϩ-sham mice showed only a modest but significant increase in myocardial triacylglycerol and 1,2-diacylglycerol levels compared with WT-sham mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duda et al (11) reported that, in a rat model of pressure overload, the increase in left ventricular mass was less marked in the FO-fed group compared with rats fed the contrast diet (rich in saturated fat). A FO diet-induced reduction in ventricular mass in a murine model of systemic carnitine deficiency (JVS mice) where cardiac enlargement occurs secondary to lipotoxicity has also been reported (45). The mechanisms leading to regression of cardiac hypertrophy in vivo remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The filtrate was centrifuged in a Millipore Microcon centrifugal filter (YM-10, 10 000 MW, Millipore) for 10 min at 12 000 g. The filtrate was assayed for total carnitine (including acylcarnitine and free carnitine) using the enzymatic cycling method (Total carnitine 'Kainos' , Kainos Laboratories, Tokyo, Japan). 22 Light and Electron Microscopy BAT samples for examination by light microscopy were fixed in 10% phosphate-buffered formalin (pH 7.4), processed into wax blocks, sectioned (4 mm thick) and stained with hematoxylin and eosin. Tissue fragments of BAT for electron microscopy were fixed with 2.5% glutaraldehyde in 0.1 M phosphate buffer, pH 7.4.…”
Section: Total Carnitine Assaymentioning
confidence: 99%